马来西亚华社对中国“一带一路”倡议的回 应：以《星洲日报》《南洋商报》《东方日 报》的报导为研究 (The Responses Of Malaysian Chinese Society To China’s Belt And Road Initiative Based On News Reports Of Sinchew Daily, Nanyang Siang Pau And Oriental Daily News) - Luo, Li (2019)
This research is to examine the perception from the Malaysian Chinese Community towards the program of “The Belt and Road” being introduced by China, and subsequently reveal the possible actions carried out by the particular community group in order to build and retain a strong diplomatic bond between both countries. The overall analysis of this paper is conducted based on the articles obtained from “Sin Chew Daily”, “Nanyang Business Daily” and “Oriental Daily” in year 2016 and 2017, where there are total 5101 feedbacks being reveal in the articles. The statistical analysis on the collected data is performed with the use of social science statistical SPSS software. The analysis has revealed the responses from the Chinese Organization and reputable Chinese in Malaysia to the implementation of “The Belt and Road”, which also indicates their respective perceptions and doubts to the said program. Furthermore, the analysis does highlighted the various distinct points of view and concerns by the Malaysian Chinese Community on the program of “The Belt and Road”, which in turn facilitate in drawing a conclusion and several suggestions that are feasible theoretically and practically in order to promote the interconnection between Malaysia and China, and subsequently be beneficial to both countries. This thesis consists of six chapters, where it begins with the literature review, which also clarifies the objectives of this research paper and briefly explain the research methodologies. The second chapter has outlined the historical development IV and interaction between the Malaysian Chinese Community with China in the past, which then followed by the introduction of the program of “The Belt and Road” and its implications towards the diplomatic relationship between Malaysia and China. From chapter 3 until 4 , the data collection of this research paper is being explained, which subsequently followed by the discussion on the result obtained, where the discussion is surrounded with the feedbacks given by the Malaysian Chinese Community in 2016 and 2017. The fifth chapter concludes the overall result of this research paper, and subsequently provides a relevant theoretical and practicable perspectives；The last chapter is make thesis’ opinions and suggestions.